2016
DOI: 10.1097/bot.0000000000000643
|View full text |Cite
|
Sign up to set email alerts
|

Case-Match Controlled Comparison of Minimally Invasive Plate Osteosynthesis and Intramedullary Nailing for the Stabilization of Humeral Shaft Fractures

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…Davis et al reported a better outcome of MIPO as compared to IMN in a total of 30 patients in 2016 [33]. Several meta-analyses reported that MIPO is a better treatment option than conventional treatment options like IMN and ORPO [34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Davis et al reported a better outcome of MIPO as compared to IMN in a total of 30 patients in 2016 [33]. Several meta-analyses reported that MIPO is a better treatment option than conventional treatment options like IMN and ORPO [34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…e rate of complications was lower than the IMN group. Davies et al [25] compared the results of MIPO and nail groups in 30 patients, and they recommended the MIPO technique as it had less complications and better functional results.…”
Section: Discussionmentioning
confidence: 99%
“…Zehir et al demonstrated that patients with mini-invasive plating had a shorter hospital stay time and bony union time than patients with intramedullary nailing [29]. It was also shown by Davies et al that MIPO was better than IMN, with a lower rate of nonunion and radial nerve injury in the treatment of humeral shaft fractures [30]. In a meta-analysis, Jia et al demonstrated both IMN and plate techniques were effective, however, nail significantly increased the risk of shoulder complications in the treatment of humeral shaft fractures [31].…”
Section: Comparison Of Postoperative Complications Between the Two Grmentioning
confidence: 97%